Pile-soil interaction under cyclic lateral load in loose sand: Experimental and numerical evaluations. Issue 162 (November 2022) - Basack, Sudip; Karami, Mehrdad; Karakouzian, Moses
Abstract: Pile foundations in loose sand are occasionally subjected to cyclic loading initiated by the influence of wind, wave, traffic loads, etc. Such load reversals alter the strength and stiffness of surrounding loose sand affecting the ultimate capacity and serviceability of the pile foundation. Although such cyclic loading may be under vertical, lateral or torsional modes or a combination, the lateral cyclic load dominates the other modes. To carry out an in-depth study on pile-soil interaction under lateral cyclic load in loose sand, a series of laboratory model tests were performed with 2 × 2 pile group, followed by developing two alternative numerical models, i.e., boundary element and finite element models (i.e., BEM and FEM). The BEM involved a p -multiplier technique to incorporate the group effect, while the FEM was developed by ABAQUS software incorporating 3D stress conditions. As observed, the BEM slightly over-predicts while the FEM marginally under-predicts the experimental observations. The lateral cyclic loading was found to produce stiffening effect on loose sand which increased the pile capacity and reduced the pile head displacement. Sand relative density is also found to affect the test and numerical results significantly. A set of important conclusions are drawn from the entire study. Highlights: Conducting laboratory model study with a new test set up on pile group response under cyclic lateral load in loose sand. Development of a numerical solution based on finite difference technique. Carrying out finite element modeling based on Abacus. Good agreement between experimental and numerical results. The cyclic pile capacity depends largely upon the cyclic loading parameters.